Complete Genome Sequence of the Facultative Methylotroph Methylobacterium extorquens TK 0001 Isolated from Soil in Poland - Belkhelfa, Sophia (Genome Announc, 2018)
Methylobacterium extorquens TK 0001 (DSM 1337, ATCC 43645) is an aerobic pink-pigmented facultative methylotrophic alphaproteobacterium isolated from soil in Poland. Here, we report the whole-genome sequence and annotation of this organism, which consists of a single 5.71-Mb chromosome.